2019
DOI: 10.1371/journal.pone.0219594
|View full text |Cite
|
Sign up to set email alerts
|

Altered individual behavioral and EEG parameters are related to the EDSS score in relapsing-remitting multiple sclerosis patients

Abstract: Functional neuroanatomy of cognitive impairment in multiple sclerosis is currently still a challenge. During the progression of the disease, several cognitive mechanisms deteriorate thus diminishing the patient’s quality of life. A primary objective in the cognitive assessment of multiple sclerosis (MS) patients is to find reliable measures utilizing diverse neuroimaging techniques. Moreover, especially relevant in the clinical environment is finding technical approaches that could be applied to individual par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…More disabilities were evident among patients with PDR frequencies lower than 4 Hz. Functional disabilities partly include the cognitive domain that is negatively associated with the progression of MS disease as indicated by functional imaging techniques [29] . Therefore, the PDR frequency correlates with cognitive function and speed of processing as indicators of cortical and subcortical lesions among MS patients.…”
Section: Discussionmentioning
confidence: 99%
“…More disabilities were evident among patients with PDR frequencies lower than 4 Hz. Functional disabilities partly include the cognitive domain that is negatively associated with the progression of MS disease as indicated by functional imaging techniques [29] . Therefore, the PDR frequency correlates with cognitive function and speed of processing as indicators of cortical and subcortical lesions among MS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have applied the visual oddball task in patients with MS [ 5 , 6 , 9 , 10 , 12 , 49 ]. Few authors have compared the performance between MS patients and healthy controls [ 9 , 10 , 49 ]. In two of these previous studies, no differences in reaction time in the visual oddball paradigm were observed between MS patients and healthy controls [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have applied the visual oddball task in patients with MS [5,6,9,10,12,49]. Few authors have compared the performance between MS patients and healthy controls [9,10,49].…”
Section: Discussionmentioning
confidence: 99%
“…ERD could be detected in persons with motor sequelae due to brain injury like stroke [21][22][23] or MS [24,25]. Furthermore, it has been shown that pwMS with moderate impairment evidence a delayed upper limb ERD-onset compared to healthy subjects [24,25]. To our knowledge, there are no reports about similar time-course analysis in lower limb ERD of pwMS.…”
Section: Introductionmentioning
confidence: 91%
“…This phenomenon is known as event-related desynchronization (ERD) [20]. ERD could be detected in persons with motor sequelae due to brain injury like stroke [21][22][23] or MS [24,25]. Furthermore, it has been shown that pwMS with moderate impairment evidence a delayed upper limb ERD-onset compared to healthy subjects [24,25].…”
Section: Introductionmentioning
confidence: 99%